Public Communication of Soviet Lithuania Targeting the Lithuanian Diaspora in the USA: Channels of Spread and Distribution Mechanisms - Ėmužienė, Ina (Lietuvos istorijos studijos, 2025)
This article examines the dissemination mechanisms and communication channels used by Soviet Lithuania to reach the Lithuanian diaspora in the United States. It focuses on the development and distribution of key propaganda tools aimed at the diaspora, including the periodicals Tėvynės balsas (renamed as Gimtasis kraštas in 1967), the domestic Soviet Lithuanian press, and foreign-directed radio broadcasts (LUL). The analysis centers on two primary channels of dissemination: first, these were Soviet Lithuanian institutions responsible for cultural relations with the diaspora, namely, the Committee for Repatriation and Cultural Relations with Compatriots Abroad (1955–1962), Lithuanian Committee for Cultural Relations with Compatriots Abroad (from 1963), and the “Tėviškė” Society (from 1976), which not only created propaganda material but also distributed it and managed diaspora subscriptions to internal Soviet publications; second, the bookstores operating in the U.S., which distributed Soviet literature and press were also used. The article also outlines the main target audiences of these efforts: the anti-communist diaspora (the so-called ‘dipukai’) and the pro-Communists, i.e., the so-called ‘progressives’.